Durable Engines of Discovery. - Dongarra, Jack (Communications of the ACM, 2025)
The article examines how U.S. federal research funding has shaped developments in computing and computational science since the 1940s. It highlights investments by federal agencies such as the National Science Foundation (NSF), the creation of the Message Passing Interface (MPI) standard, and the development of software libraries like Basic Linear Algebra Subprograms (BLAS), as well as broader impacts on economic competitiveness, industrial innovation, and workforce development.